Comparison of various gating systems for investment casting of hydraulic retarder impeller with complex geometry. (March 2021) - Li, Fei; Wang, Yingchun; Wang, Donghong; Zhao, Yanjie; Qi, Chengkang; Sun, Baode
Due to the complex structure and thin thickness of the guide vane edge of the hydraulic retarder impeller, the casting defects such as shrinkage porosity and misrun are usually formed during casting, which have a close relationship with the filling and solidification process. In this work, the filling and solidification processes of impeller in various gating systems, named case 1 to 3, were simulated and the distribution characteristics of potential shrinkage porosity defects were predicted by ProCAST software based on the mathematical models, boundary conditions, and parameters of investment casting. The simulation results show that the aim of complete filling of the impeller can be achieved by using all of the three gating systems. However, only the case 3 gating system consisted with one sprue riser and four feeding risers can provide the impeller with suitable feeding channel in melt solidification process. Therefore, no predicted shrinkage porosities form in the impeller because the defects can transfer to the gating system during solidification. The optimized gating system have been verified by experiment, and the rapid casting of the impeller has been realized by using 3D printed polystyrene patterns. The results of visual and X-ray inspections show that both the misrun and shrinkage porosity defects were eliminated in the actually final cast, which matched well with the numerical simulation results for the investment casting of the impeller. Many experiment results of the new product show that these optimization gating system are very helpful to reduce the casting defect and to improve the product quality.